Cultura Política e Polos Regionais: comparando Campos dos Goytacazes (RJ) com Maringá ampliada (PR) - Sergio de Azevedo; Celene Tonella; Joseane de Souza (Ciências Sociais Unisinos)
The article analyzes in comparative perspective the similarities and differences between the political culture of the population resident in Campos dos Goytacazes (RJ) and Maringá, Paysandú and Sarandi, set of municipalities that we call Maringá magnified. On the comparative analysis between the Regional Poles two major theoretical questions that unify the proposal of this work are prioritized. The first corresponds to the classical concerns relating to the operation of democracy and citizens’ participation in the public life. The second refers to the impacts that the processes of change, differentiation and trajectory of life impacted in different groups, personal values that present, in different ways, an arc that goes from traditional conservatism to the legitimization of new habits and posture.